Is Therapeutic Drug Monitoring Relevant for Antidepressant Drug Therapy? Implications From a Systematic Review and Meta-Analysis With Focus on Moderating Factors - Funk, Cleo S. M.; Hart, Xenia M.; Gründer, Gerhard; Hiemke, Christoph; Elsner, Björn; Kreutz, Reinhold; Riemer, Thomas G. (Frontiers in Psychiatry, 2022)
Inter-individual differences in antidepressant drug concentrations attained in blood may limit the efficacy of pharmacological treatment of depressive disorders. Therapeutic Drug Monitoring (TDM) enables to determine drug concentrations in blood and adjust antidepressant dosage accordingly. However, research on the underlying assumption of TDM, association between concentration and clinical effect, has yielded ambiguous results for antidepressants. It has been proposed that this ambiguity may be caused by methodological shortcomings in studies investigating the concentration-effect relationship. Guidelines recommend the use of TDM in antidepressant treatment as expert opinion. This reflects the lack of research, particularly systematic reviews and meta-analyses of randomized controlled trials, on the relationship between concentration and effect as well as on the benefits of the use of TDM in clinical practice. In this study, a systematic review and meta-analysis of randomized controlled trials has been performed to investigate the relationship between antidepressant concentration, efficacy, and side effects. It is the first meta-analytical approach to this subject and additionally considers methodological properties of primary studies as moderators of effect in quantitative analysis. Our results identified methodological shortcomings, namely the use of a flexible dose design and the exclusion of concentrations in lower- or subtherapeutic ranges, which significantly moderate the relationship between antidepressant concentration and efficacy. Such shortcomings obscure the evidence base of using TDM in clinical practice to guide antidepressant drug therapy. Further research should consider these findings to determine the relationship between concentration and efficacy and safety of antidepressant treatments, especially for newer antidepressants.